KEABSAHAN SMART CONTRACT TERKAIT PEMBERLAKUAN ANONIMITAS DALAM TRANSAKSI NON-FUNGIBLE TOKEN (NFT) - Belva Syahda Mahardika (2023)
Along with the times, technology is shifting to the use of electronic-based systems, as well as agreements. Where, initially only able to use agreements on paper, or in conventional form, shifted to electronic-based agreements, or can also be referred to as smart contracts. Smart contracts themselves have an agreement clause in the form of a code, where the code can only be read by the computer system. Generally, smart contracts are used as a medium for buying and selling digital materials, such as NFTs. However, in the use of smart contracts for buying and selling NFTs, there is a nature of anonymity towards the parties, which is still not in accordance with the subjective terms of the agreement contained in Article 1320 of the Civil Code, namely the existence of a form of proficiency from legal subjects. Therefore, the purpose of this study is to determine the legal validity of the existence of anonymity in the smart contract. The research method used in this writing is to use normative juridical methods.